Alterations in molecular muscle mass regulators after 8 days immobilizing Special Forces mission. Issue 2 (15th January 2014) - Jespersen, J. G.; Mikkelsen, U. R.; Nedergaard, A.; Thorlund, J. B.; Schjerling, P.; Suetta, C.; Christensen, P. A.; Aagaard, P.
Abstract : In military operations, declined physical capacity can endanger the life of soldiers. During special support and reconnaissance (SSR) missions, Special Forces soldiers sustain 1–2 weeks full‐body horizontal immobilization, which impairs muscle strength and performance. Adequate muscle mass and strength are necessary in combat or evacuation situations, which prompt for improved understanding of muscle mass modulation during SSR missions. To explore the molecular regulation of myofiber size during a simulated SSR operation, nine male Special Forces soldiers were biopsied in m. vastus lateralis pre and post 8 days immobilizing restricted prone position. After immobilization, total mammalian target of rapamycin protein was reduced by 42% ( P  < 0.05), whereas total and phosphorylated protein levels of Akt, ribosomal protein S6k, 4E‐BP1, and glycogen synthase kinase3β were unchanged. Messenger RNA (mRNA) levels of the atrogenes forkhead box O3 (FoxO3), atrogin1, and muscle ring finger protein1 (MuRF1) increased by 36%, 53%, and 71% ( P  < 0.01), MuRF1 protein by 51% ( P  = 0.05), whereas FoxO1 and peroxisome proliferator‐activated receptor γ coactivator‐1 β mRNAs decreased by 29% and 40% ( P  < 0.01). In conclusion, occupational immobilization in Special Forces soldiers led to modulations in molecular muscle mass regulators during 8 days prone SSR mission, which likely contribute to muscle loss observed in such operations. The present data expand our knowledge of human muscle mass regulation during short‐term immobilization.